The estimation of dynamical distribution of domesticated Burgo chicken population in Bengkulu coastal area, Indonesia - HERI DWI PUTRANTO; GADING PUTRA HASIBUAN; YOSSIE YUMIATI; JOHAN SETIANTO; BIENG BRATA; NOVITRI KURNIATI; FITRIAN FAJAR HAKIKI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Putranto HD, Hasibuan GP, Yumiati Y, Setianto J, Brata B, Kurniati N, Hakiki FF. 2017. The estimation of dynamical distribution of domesticated Burgo chicken population in Bengkulu coastal area, Indonesia. Biodiversitas 18: 458-464. As one of the endemic bird species, which inhabits on the west coast of Sumatra and southern Sumatra region, such as Bengkulu Province, Jambi Province and South Sumatra Province, Burgo chicken is recognized as a pet and a socio-economic symbol status for fanciers. The study aimed to monitor the dynamical distribution of male Burgo population domesticated by fanciers in three regencies and a city located along the coastal area of Bengkulu Province. The locations were determined by a purposive sampling method. By using the software in the form of online questionnaire program, enumerators conducted a field survey for 4 weeks in July-August 2016 by a purposive sampling in three regencies and a city, i.e. Bengkulu City, Seluma District, Bengkulu Utara District and Bengkulu Tengah District. The datas obtained in the field were connected and stored in the system provided on a page and could be accessed in a limited basis. Furthermore, the population datas were summarized and analyzed by using a Variance-Mean Ratio (VMR) formula to determine the distribution pattern of domesticated male Burgo chicken. The results showed that in the year of 2016 the highest population of male Burgo chicken (53.29% population) was found in Bengkulu Utara District as many as 89 individuals, while the lowest population (1.19% or 2 individuals) was found in Seluma District. Furthermore, it was also known that the distribution of domesticated male Burgo population in the coastal area of Bengkulu Province could be classified as negative binomial distribution or over-dispersed (VMR>1.0). The results of estimation of dynamical distribution pattern of male Burgo chicken population in year of 2016 in the coastal areas of Bengkulu Province was similar to the distribution pattern of mixed sex Burgo chicken population in Bengkulu Province in year of 2009 which was categorized as negative binomial distribution. Keywords: Burgo, coastal, distribution, dynamic, population